Dietary patterns associated with benign breast nodules by subtypes: a cross-sectional study in southeast China - Zhu, Pingxiu; He, Mei; Gong, Jiamin; Su, Qingling; Feng, Ruimei; Cai, Yundan; Qiu, Weihong; Yang, Haomin; Du, Shanshan; Ye, Weimin (Frontiers in Nutrition, 2025)
BackgroundDietary patterns influence women's risk of breast cancer, but few studies have investigated the association with benign breast nodules, a well-established risk factor for breast cancer, especially by subtypes of the disease.MethodsA cross-sectional study of 3,483 women enrolled in the Fuqing Cohort Study in southeast China was conducted from 2020 to 2021. Dietary patterns were identified from food frequency questionnaires using principal component analysis, and the scores for these patterns were divided into quartiles. Univariate and multivariate logistic regression models were used to calculate odds ratios (OR) with 95% confidence interval (CI) for the association between dietary patterns and benign breast nodules.ResultsWe found four dietary patterns among the women: animal-based dietary pattern, plant-based dietary pattern, fried food/dessert pattern, and nuts pattern. Compared with the lowest quartile, women in the highest quartile of the scores for the animal-based dietary pattern were more likely to have cystic breast nodules (OR = 1.61, 95% CI = 1.12–2.32, and the P-value for trend test = 0.007), especially in postmenopausal women. In addition, women with a high score for fried food/dessert pattern also had higher odds of breast cystic nodules (P-value for trend test = 0.012), with an OR (95% CI) of 1.46 (1.01–2.09) for the fourth quartile group. However, there were no associations between these dietary patterns and solid breast nodules.ConclusionAnimal-based dietary pattern and fried food/dessert pattern were positively associated with cystic breast nodules. These findings suggested the role of unhealthy dietary habits in the development of breast nodules.